Synthesis and gastric ulcer protective activity of chlorinated quercetin - Gusdinar, Tutus; Herowati, Rina; Kartasasmita, R. E.; Adnyana, I Ketut (Indonesian Journal of Pharmacy, 2009)
Gastrointestinal toxicity due to non-steroid anti-inflammatory drugs can be inhibited by the compounds that have antioxidant activity. Quercetin is a flavonoid that has antioxidant activity and protection effect against gastric ulcer. Chlorination of quercetin enhanced the antioxidant activity. This study aims to obtain the chlorinated derivative of quercetin and examine the protection effect against acetosal-induced gastric ulcer. Chlorination was done by the addition of chlorine at room temperature. Ulcer induction was carried out on rats by oral administration of acetosal. Incidences of gastric ulcer were determined by macroscopic and microscopic observation. Chlorination of quercetin with chlorine gas produced 6-chloroqueretin as major product. The protection effect against acetosal-induced gastric ulcer of this compound was higher than quercetin.Key words : quercetin, chlorination, gastric ulcer, NSAIDs